Unified Retrocausal Theory of Fundamental Interactions and Gravity by the Temporal Coherence Field Λ(x,t) - Amine Chbihi Moukit (My University, 2025)
Unified Theory, RG, quantic, cosmology, Dirac, Higgs, Lagrangien, dark hole, Gauge, QCD, unification of fundamental interactions